Vaccinations in Pregnancy. A Comprehensive Overview - Plewniok, Ines; Maj-Dziedzic, Monika; Sikora, Marcelina; Zarzycka, Marta; Brzozowska, Anna; Dubiel, Jeremiasz; Maj, Adrian; Warno, Martyna; Kozik, Wiktor; Śmietana, Greta (Journal of Education, Health and Sport, 2024)
Introduction and purpose Pregnancy is associated with many changes in the mother's body, allowing for the proper development of the fetus, but unfortunately it also predisposes many potentially harmless infections to become much more severe during pregnancy. Therefore, vaccinations during pregnancy play a very important protective role both for the mother, her unborn child and to the child immediately after birth. Immunization during pregnancy and in the preconception period protects against many infectious diseases and related complications. By receiving the vaccine, specific antibodies are synthesized and transported across the placenta to the fetus. They protect the baby during the first months of life, when the baby cannot receive vaccinations due to its age yet. Vaccinations during pregnancy can be divided into necessary, possible and recommended. Recommended vaccinations include against diphtheria, tetanus, pertussis, influenza, Covid19 and RSV. They are especially recommended for every pregnant woman who has no permanent or temporary contraindications. A special group of vaccinations are those necessary to perform, which play the main role as post-exposure prophylaxis and must be administered immediately after exposure to the agent causing the infection. These include mainly vaccination against tetanus and rabies. The vaccinations that can be performed include those targeted at a specific group of patients with various chronic diseases who are at risk or traveling to countries where there is an increased risk of illness. During a doctor's visit to a woman planning a pregnancy, it is important to collect a detailed interview regarding vaccination history, past infectious infections and chronic diseases. This allows us to prepare an individualized vaccination schedule recommended both before and during pregnancy.